1996
DOI: 10.1002/(sici)1098-1063(1996)6:3<306::aid-hipo8>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic target selectivity and input of GABAergic basket and bistratified interneurons in the CA1 area of the rat hippocampus

Abstract: To assess the position of interneurons in the hippocampal network, fast spiking cells were recorded intracellularly in vitro and filled with biocytin. Sixteen non‐principal cells were selected on the basis of 1) cell bodies located in the pyramidal layer and in the middle of the slice, 2) extensive labeling of their axons, and 3) a branching pattern of the axon indicating that they were not axo‐axonic cells. Examination of their efferent synapses (n = 400) demonstrated that the cells made synapses on cell bodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(99 citation statements)
references
References 76 publications
(121 reference statements)
3
94
0
1
Order By: Relevance
“…In the tissue derived from tumor-induced epileptic tissue (in which the GABA release experiments have been done), we found that almost one-third of the CB1-positive cells were negative for CCK. In contrast, the absolute number and size of the boutons may vary widely across different interneuron types, 12,16,30 which likely correlates with the amount of released GABA, and may also explain the discrepancy between the quantitative data of the anatomical and pharmacological experiments.…”
Section: Cb1 Cannabinoid Receptor Activation Leads To a Reduction Of mentioning
confidence: 98%
“…In the tissue derived from tumor-induced epileptic tissue (in which the GABA release experiments have been done), we found that almost one-third of the CB1-positive cells were negative for CCK. In contrast, the absolute number and size of the boutons may vary widely across different interneuron types, 12,16,30 which likely correlates with the amount of released GABA, and may also explain the discrepancy between the quantitative data of the anatomical and pharmacological experiments.…”
Section: Cb1 Cannabinoid Receptor Activation Leads To a Reduction Of mentioning
confidence: 98%
“…18,37,86,102 This connectivity feature allows synchronous inhibition of a multitude of pyramidal cells; the estimated numbers range from several hundred up to 2,500 cells. 85,103,104 Together with the dendritictargeting interneurons, the pattern of convergence and divergence in hippocampal network connectivity thus reflects the intense feed-forward and feedback control of principal cells by GABAergic inhibition. 17,37,101,105,106 Importantly, PV þ basket cells and axo-axonic cells strongly increase their spiking rate during specific oscillating network states of the hippocampus, especially during theta-, gamma-, and ripple oscillations.…”
Section: Hippocampal Gamma Oscillations and Fast-spiking Inhibitory Imentioning
confidence: 99%
“…Recent in vitro and in vivo studies using intracellular labeling methods have identified several hippocampal CA1 interneuron types and have classified them according to their input and output features (Buhl et al, 1994;McBain et al, 1994;Sik et al, 1995;Freund and Buzsáki, 1996;Halasy et al, 1996;Maccaferri and McBain, 1996). Numerous physiological recordings were obtained from interneurons in this hippocampal subfield, but only two groups of dendritic inhibitory cells, namely bistratified cells and O-LM cells (Buhl et al, 1994;McBain et al, 1994;Sik et al, 1995;Halasy et al, 1996), have been morphologically characterized in detail.…”
Section: Novel Type Of Hippocampal Ca1 Interneurons With Axonal Arbormentioning
confidence: 99%
“…Numerous physiological recordings were obtained from interneurons in this hippocampal subfield, but only two groups of dendritic inhibitory cells, namely bistratified cells and O-LM cells (Buhl et al, 1994;McBain et al, 1994;Sik et al, 1995;Halasy et al, 1996), have been morphologically characterized in detail. These cell types have been confirmed in our study as well.…”
Section: Novel Type Of Hippocampal Ca1 Interneurons With Axonal Arbormentioning
confidence: 99%